Minithoracotomy and Beating Heart Strategy for Mitral Surgery in Secondary Mitral Regurgitation - Grinberg, Daniel; Pozzi, Matteo; Bordet, Marine; Nouhou, Kaled Adamou; Kwon, Young Joon; Obadia, Jean-François; Vola, Marco (The Thoracic and Cardiovascular Surgeon, 2019)
Background In patients with secondary mitral regurgitation (MR) associated with low ejection fraction or previous heart surgery, minimally invasive mitral valve surgery without aortic cross-clamp (MIMVS-WAC) has shown promising results. We report our experience for this strategy in our centers.Methods Between August 2011 and April 2017, 46 patients (mean age 69 ± 11 years, 76% males) received MIMVS-WAC. Indications for this technique were prior coronary bypass surgery (26%), severe or recent left ventricular (LV) dysfunction (30%), or both (39%). The mean EuroSCORE II was 12 ± 10.Results For each procedure, we conducted right minithoracotomy and hypothermic cardiopulmonary bypass (CPB) after peripheral cannulation. Mean CPB time was 159 ± 39 minutes. A mitral valve replacement (MVR) was performed in 23 cases (50%), an annuloplasty in 22 cases (48%), and a prosthesis pannus removal in 1 case (2%). Mean hospital length of stay was 12 ± 5.4 days. We report no sternotomy conversions, six reoperations for bleeding, and three deaths at 30 days. Transfusion was requested in 62% (mean infusion 2 ± 2.4 packed red blood cells). The postoperative echocardiography showed an LV function preservation in 69% of cases and a reduction of pulmonary arterial pressure in 73% of cases. Four additional deaths occurred in the long-term follow-up (mean 637 ± 381 days, median 593 days). No mitral reoperation was required, with a MR ≤ 2 in 90% of patients.Conclusion In high-risk patients, the MIMVS-WAC is a safe technique. It avoids hard dissections while ensuring excellent preservation of cardiac function.
Keywords: mitral valve surgery; minimally mitral invasive surgery; beating heart; high risk surgery